Comparative gene expression analysis of Dtg, a novel target gene of Dpp signaling pathway in the early Drosophila melanogaster embryo. - Hodar, C.; Zuñiga, A.; Pulgar, R.; Travisany, D.; Chacon, C.; Pino, M.; Maass, A.; Cambiazo, V. (Gene, 2014)
In the early Drosophila melanogaster embryo, Dpp, a secreted molecule that belongs to the TGF-? superfamily of growth factors, activates a set of downstream genes to subdivide the dorsal region into amnioserosa and dorsal epidermis. Here, we examined the expression pattern and transcriptional regulation of Dtg, a new target gene of Dpp signaling pathway that is required for proper amnioserosa differentiation. We showed that the expression of Dtg was controlled by Dpp and characterized a 524-bp enhancer that mediated expression in the dorsal midline, as well as, in the differentiated amnioserosa in transgenic reporter embryos. This enhancer contained a highly conserved region of 48-bp in which bioinformatic predictions and in vitro assays identified three Mad binding motifs. Mutational analysis revealed that these three motifs were necessary for proper expression of a reporter gene in transgenic embryos, suggesting that short and highly conserved genomic sequences may be indicative of functional regulatory regions in D. melanogaster genes. Dtg orthologs were not detected in basal lineages of Dipterans, which unlike D. melanogaster develop two extra-embryonic membranes, amnion and serosa, nevertheless Dtg orthologs were identified in the transcriptome of Musca domestica, in which dorsal ectoderm patterning leads to the formation of a single extra-embryonic membrane. These results suggest that Dtg was recruited as a new component of the network that controls dorsal ectoderm patterning in the lineage leading to higher Cyclorrhaphan flies, such as D. melanogaster and M. domestica.